Hydrophilic Matrix Based Oral Controlled Release Tablets of Melt Sonocrystallized Simvastatin - Surendra Tripathy, Brijesh Kumar Singh, Dilip Kumar Patel, Narahari Narayan Palei (Journal of Applied Pharmaceutical Science, 2016)
The major drawback of Simvastatin to formulate a dosage form is its poor aqueous solubility. In this study a solvent and carrier less technique called Melt sonocrystallization was utilized to form tiny crystals of Simvastatin with enhanced solubility in distilled water and Phosphate buffer pH 7.4, with an insignificant (p > 0.05) change in partition behaviour. The Melt sonocrystallized Simvastatin (MSCSIM) was characterized by FT-IR, DSC and SEM. The flow property was characterized and compared with pure Simvastatin. The MSCSIM was incorporated in directly compressed matrix tablets formed with varying proportion of HPMC K100 LV and starch. The formed tablets were evaluated for pharmacotechnical parameters along with drug release study. After melt sonocrystallization the chemical integrity of drug was unchanged and showed a sound flow property. The pharmacotechnical features of the tablets were noted to be within pharmacopoeial limit. The formulation F5 displayed a comparatively more controlled release of drug (96.45%) over 12 hours. The major release mechanism was found to be anomalous diffusion, with n value of 0.58 from the Korsmeyer-Peppas model, suggesting the drug release driven by swelling of matrix and diffusion. This technique may prove to be beneficial for poorly water soluble drugs and the melt sonocrystallized drugs can lend themselves for developing controlled release formulations.
Keywords: Simvastatin, Meltsonocrystallization, Solubility, Matrix, Controlled release.